Reclaiming the Educative Power of Vocational Placements: Experiences from Agriculture Education Practice in Uganda - Jjuuko, Robert; Tukundane, Cuthbert; Zeelen, Jacques (International Journal of Training and Development, 2021)
Amidst the global pressure on education systems to harness youth employability and transition to the world of work, there is increased interest in vocational placements. It is evident that Uganda's tertiary education sector, like others in similar context, is struggling to optimise vocational placements for better students’ learning and labour market outcomes. This article explores the “educative” potential of vocational placements offered as a component of study programmes by a public tertiary agricultural training institution in Uganda. It draws on data generated from a qualitative case study that engaged 70 stakeholders namely students, graduates, lecturers, administrators and workplace supervisors. Undertaken between 2016 and 2019, the study reveals the complexities and prospects associated with the design and delivery of vocational placements in stressed education and labour market contexts. From a social constructivist perspective, we make contextual pedagogical propositions for unleashing the educative power of vocational placements in Uganda and similar contexts.
Keywords: agricultural education; vocational placements; workplace learning